2012
DOI: 10.1017/s1041610212001482
|View full text |Cite
|
Sign up to set email alerts
|

Relative preservation of the recognition of positive facial expression “happiness” in Alzheimer disease

Abstract: In AD patient, recognition of happiness was relatively preserved; recognition of happiness was most sensitive and was preserved against the influences of age and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 28 publications
(39 reference statements)
3
54
1
1
Order By: Relevance
“…Consistently, Wiechetek and his colleagues [67] also found that AD patients preserved the recognitions of happy but not fear or disgust faces. By adopting a sophisticated matching task, a recent study [68] showed that only the abilities to recognize happy but not sad or angry faces were relatively preserved among early AD patients. Given the association between the ability to recognize happy faces and positive emotions, the researchers posited that early AD patients might use this as an emotion regulatory strategy to increase positive emotions.…”
Section: Positivity Bias On Early Ad's Emotional Perceptionmentioning
confidence: 99%
“…Consistently, Wiechetek and his colleagues [67] also found that AD patients preserved the recognitions of happy but not fear or disgust faces. By adopting a sophisticated matching task, a recent study [68] showed that only the abilities to recognize happy but not sad or angry faces were relatively preserved among early AD patients. Given the association between the ability to recognize happy faces and positive emotions, the researchers posited that early AD patients might use this as an emotion regulatory strategy to increase positive emotions.…”
Section: Positivity Bias On Early Ad's Emotional Perceptionmentioning
confidence: 99%
“…This attention bias for positive information is believed to improve memory (the so-called positivity effect), as the more information is attended, the more likely it is to be remembered later on (Carstensen, 2006). Regarding aMCI and AD,research on the impact of emotion and/or valence on memoryhas provided mixed results, reporting either an effect of emotion (Giffard, Laisney, Desgranges, & Eustache, 2015; ), no effect of emotion(Abrisqueta-Gomez, Bueno, Oliveira, & Bertolucci, 2002;Kensinger, Brierley, Medford, Growdon, & Corkin, 2002), an effect of positive valence (Kalenzaga, Piolino, & Clarys, 2014;Maki, Yoshida, Yamaguchi, & Yamaguchi, 2013;Werheid, McDonald, Simmons-Stern, Ally, & Budson, 2011;Werheid et al, 2010) or an effect of negative valence Döhnel et al, 2008;Boller et al, 2002). The question of whether the effect of emotionally-laden material on memory is maintained through self-reference across the spectrum of ADpathology still requires much more investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, for non-facial stimuli, both dementia groups had prolongation of gaze to negative pictures. The reason for this is not clear, but may be partially explained by an impaired ability in specifically recognizing stimuli with negative emotion [22][23][24][25]. The patients may spend their time longer trying to interpret what they cannot recognize.…”
Section: Discussionmentioning
confidence: 99%